Issue of holocaust: school of functionalist and internationalist - Berenis, Vytautas (Genocidas ir rezistencija, 2001)
Historiographical schools of ‘intentionalists’ and ‘functionalists’ and their theoretical premises were formed in the 1950s to 1970s in German and Anglo–Saxon science of history under the banner of ‘historicism’. Its aim was to reveal the causes of the ideology of national socialism, the rise of the Nazis to power, and to show the genesis of the mechanism of mass annihilation of people (mainly Jews).
Keywords: Holocaust; nationalsocialism; Jews